Influence of Internal Corporate Communication on Employee’s Job Performance Improvement (Journal of Management and Social Sciences, 2022)
Effective communication has been linked to positive outcomes in organizational success and employee’s job output. However, the inability of managers to effectively communicate with their employees leads to employee job dissatisfaction and poor performance. Hence, this study examines how internal corporate communication influences employees’ job output in selected organizations. The quantitative and qualitative methods were adopted to gather data. Two ninety-six (296) copies of questionnaire were administered to junior and senior personnel of the selected organizations while in-depth interview was conducted with selected management level personnel. Quantitative data were analyzed using simple frequency percentages while qualitative data were coded along thematic lines. The majority of the employees agreed that the internal corporate communication in their organizations influenced their job output. Also, the majority of the employees agreed that management communication style influences employee job satisfaction towards performance. The organizations are faced with diverse internal communication challenges such as distorted feedback, matching message content with appropriate packaging, inadequate information, uneven flow of information etc. These challenges, when not properly tackled, can hinder many organizational processes, especially its efforts at achieving employee job satisfaction/performance.  Keywords    Internal corporate communication, employees’ job output, management communication style